Analysis of 4C Principles and Credit Eligibility of People's Businesses (Case Study on MSMEs Built by Mandiri BUMN House, Bogor) - Astuti, Wiji; Nidar, Sulaeman Rahman; Faisal, Yudi Ahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Less than 10% of Micro and Small Enterprises (MSEs) under the member of Rumah BUMN Mandiri, Bogor have successfully obtained Kredit Usaha Rakyat (KUR) from formal financial institutions. This study aims to determine the influence of the 4C Principles; character, capacity, capital, and condition, on the eligibility status for granting KUR to MSEs under the member of Rumah BUMN Mandiri, Bogor, and to formulate a business incubation program scheme based on the concept of Integrated Microfinance Management (IMM). The quantitative approach used is an independent t-test and Structural Equation Modeling (SEM), while the qualitative approach is conducted through thematic analysis. Data collection is carried out using purposive sampling through questionnaires distributed to 109 MSEs under the member of Rumah BUMN Mandiri, Bogor, and in-depth interviews with informed respondents. The research results indicate that the aspects of character, capacity, and condition significantly influence the eligibility status for KUR, while the capital aspect does not have a significant influence. There is a need for synergy between Rumah BUMN Mandiri, Bogor, and Bank Mandiri to increase the number of KUR recipients through an entrepreneurship empowerment program oriented towards achieving the output and outcome of the business incubation process, as well as effective socialization of business credit management.